Formulation and evaluation of mucoadhesive buccal tablets of montelukast sodium - Soumik Ghosh; Pawan Kumar; Satyabrata Bhanja; Nansri Saha; Sarita Tiwari (International Journal of Pharmacy and Analytical Research, 2022)
The objective of this study was to develop effective mucoadhesive buccal tablets of Montelukast sodium prepared by direct compression method using bioadhesive polymers like Xanthan gum, Tamarind gum and synthetic polymers like HPMC K15M,HPMC K100M and sodi um CMC as a muco adhesive polymer. Buccal tablets were evaluated by different methods for parameters such as thickness, hardness, weight uniformity, content uniformity, swelling index, in vitro bioadhesive strength, in vitro drug release, stability studies in human saliva, in vivo mucoadhesive performance studies. Bioadhesion strength was increased with increase in the concentration of the polymer, higher bioadhesion strength was found in HPMC K100M. The tablets were evaluated for in vitro release in pH 6.8 phosphate buffer for 12 hr in standard dissolution apparatus. When compared with natural and synthetic polymers sustained drug release was found with synthetic polymer HPMC K100M(60mg) along with sodium CMC as a mucoadhesive polymer.The stability studies indicated that there was no significant change in drug release after 3months.